Modelling the efficiency of a low-profile nanofluid-based direct absorption parabolic trough solar collector. (November 2018) - O'Keeffe, G.J.; Mitchell, S.L.; Myers, T.G.; Cregan, V.
Highlights: We design and model three types of nanofluid-based direct absorption solar collector. We non-dimensionalise the model revealing seven controlling dimensionless numbers. We solve the system via a novel modification to the Crank-Nicolson method. A parameter space exploration is conducted to investigate the optimal design. Abstract: This paper compares the performance of three variations to a novel low-profile nanofluid-based direct absorption parabolic trough solar collector design. More specifically, we propose a steady state, three-dimensional model for the efficiency of such a collector subject to laminar flow. The model consists of a system of two partial differential equations describing the conservation of energy and momentum, and a radiative transport equation describing the propagation of radiation through the nanofluid. We non-dimensionalise the model revealing seven controlling dimensionless numbers: two describing different rates of thermal diffusion to advection, another two describing Newton cooling at the boundaries, and the remaining three describing black-body emissions at the boundaries. The system is solved via a modified Crank-Nicolson method which is optimised to cater for non-linearities in the radiative transport equation. A realistic parameter space exploration is conducted to investigate the optimal collector design variation.